Uji Valditas dan Reliabilitas Keseimbangan Dinamis The Timed Up and Go Test pada Pasien Stroke - Nadhirah, Sabina Azka; Sari, Dwi Rosella Komala (Poltekkes Kemenkes Kupang, 2024)
Background: Stroke is a brain disease from local and globalnervous function disorders. Strokes appear suddenly,progressively, and rapidly. Decreased balance results in a highrisk of falling and can be detected using the Timed Up and Gotest (TUG). Objective: This study aims to determine the validityand reliability of TUG in terms of intra-rater and inter-rater.This research was carried out at a Government hospital atBoyolali, Central Java, with a population of 36 chronic strokepatients. Methods: This study used an observational studywith methodological research. Results: The Cronbach's alphaof intra-rater and inter-rater reliability of the TUG were morethan 0.9, with both ICC were also more than 0.9. The Pearsonproduct-moment between tests 1 and 2 revealed asignificantly very high correlation (p<0.001 and r=0.986). TheTUG showed high validity and reliability for intra-rater andinter-rater for stroke patients to measure dynaimc balance instroke patients.